Characterization of spatial-mode properties in few-mode fiber BRAGG gratings and its applications / Muhammad Khairol Annuar Zaini - Muhammad Khairol Annuar , Zaini (2021)
Recently, few-mode fiber (FMF) has gained much research attention compared to single mode fiber (SMF) due to its capability to overcome the capacity limit. FMF based fiber sensors have many distinctive advantages such as cost efficiency, great sensitivity, and have the ability to employ the spatial dimension for multi-parameter sensing with discrimination capability. In this work, an analytical model has been proposed to investigate the relationship of the resonant wavelength shift of a few-mode FBG (FMFBG) to the axial stress of the FMF. By applying the proposed model, the axial stress of an FMFs was determined. Besides, the polariscopic technique for measuring the reference stress profile of the FMFs has been described. Based on the experimental results, it can be seen that the axial stress in the fiber cladding determined by using the proposed model fits well with the polariscopic measurement. Therefore, the determination of the axial stress of the FMFs was accomplished based on the resonant wavelength shifts during the chemical etching process. Furthermore, a comparative analysis of two different signal processing techniques is carried out to identify the multiple reflection wavelength peaks of the etched FMFBG sensor. Modal effective indices in FMF have been numerically computed to determine the self- and cross-mode coupling resonant wavelengths in FMFBGs. After that, the chemical etching process has been performed to fabricate an etched FMFBG for the investigation of modal sensitivities. For all the acquired spectra both of the techniques such as conventional peak detection (CPD) and digital matched filter (DMF) have been applied to examine the more accurate sensitivity of the sensor for RI and temperature. It has been shown that the DMF gives a better performance in the measurement accuracy as compared to CPD. In addition, a 3×3 order characteristic matrix has been used to suppress the effect of the cross sensitivity issue. Hence it is clear that the etched FMFBG can be used as multi-parameter with enhanced performance by DMF technique. Moreover, based on mode conversion inside FMFBGs an optical delay system is constructed. A pair of FMFBGs are served as selective mode converters. The time delay introduced by the few-mode delay line with different FMF segment lengths has been theoretically and experimentally investigated. It depends on the chosen configuration based on laser operating wavelength of the input pulse stream and the resultant accumulated optical path length in the FMF. Besides, the shift of the relative phase of LP11o and LP11e modes with respect to LP01 when a section of two-mode fiber (TMF) was heated to a different temperature in the range of 26-34˚C is demonstrated. Based on the mode profile recorded at the TMF output, the relative phase has been determined